HIV Tat as a latency reversing agent: turning the tables on viral persistence - Fisher, Bridget M.; Cevaal, Paula M.; Roche, Michael; Lewin, Sharon R. (Frontiers in Immunology, 2025)
The ‘shock and kill’ approach to an HIV cure involves the use of latency reversing agents (LRAs) to reactivate latent HIV, with the aim to induce death of infected cells through virus induced cytolysis or immune mediated clearance. Most LRAs tested to date have been unable to overcome the blocks to transcription elongation and splicing that persist in resting CD4+ T cells. Furthermore, most LRAs target host factors and therefore have associated toxicities. Therefore, there remains a high need for HIV-specific LRAs that can also potently upregulate expression of multiply-spliced HIV RNA and viral protein. The HIV Transactivator of Transcription (Tat) protein plays an important role in viral replication - amplifying transcription from the viral promoter - but it is present at low to negligible levels in latently infected cells. As such, it has been hypothesized that providing Tat in trans could result in efficient HIV reactivation from latency. Recent studies exploring different types of Tat-based LRAs have used different nanoparticles for Tat delivery and describe potent, HIV-specific induction of multiply-spliced HIV RNA and protein ex vivo. However, there are several potential challenges to using Tat as a therapeutic, including the ability of Tat to cause systemic toxicities in vivo, limited delivery of Tat to the HIV reservoir due to poor uptake of nucleic acid by resting cells, and challenges in activating truly transcriptionally silent viruses. Identifying ways to mitigate these challenges will be critical to developing effective Tat-based LRA approaches towards an HIV cure.